A GaN/InGaN/AlGaN MQW RTD for versatile MVL applications with improved logic stability *Project supported by the National Natural Science Foundation of China (Nos. 61302009, 61571171). (July 2018) - Zhang, Haipeng; Zhang, Qiang; Lin, Mi; Lü, Weifeng; Zhang, Zhonghai; Bai, Jianling; He, Jian; Wang, Bin; Wang, Dejun
Abstract: To improve the logic stability of conventional multi-valued logic (MVL) circuits designed with a GaN-based resonate tunneling diode (RTD), we proposed a GaN/InGaN/AlGaN multi-quantum well (MQW) RTD. The proposed RTD was simulated through solving the coupled Schrodinger and Poisson equations in the numerical non-equilibrium Green's function (NEGF) method on the TCAD platform. The proposed RTD was grown layer by layer in epitaxial technologies. Simulated results indicate that its current-voltage characteristic appears to have a wider total negative differential resistance region than those of conventional ones and an obvious hysteresis loop at room temperature. To increase the Al composite of AlGaN barrier layers properly results in increasing of both the total negative differential resistance region width and the hysteresis loop width, which is helpful to improve the logic stability of MVL circuits. Moreover, the complement resonate tunneling transistor pair consisted of the proposed RTDs or the proposed RTD and enhanced mode HEMT controlled RTD is capable of generating versatile MVL modes at different supply voltages less than 3.3 V, which is very attractive for implementing more complex MVL function digital integrated circuits and systems with less devices, super high speed linear or nonlinear ADC and voltage sensors with a built-in super high speed ADC function.